(untitled) (Bangladesh Journal of Botany, 2014)
Analysis of organic solvent extracts of Enicostemma littorale reveals the presence of total phenols, vitamin C and E and carbohydrates. The organic solvent extracts of E. littorale exhibited antibacterial activities. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18046 Bangladesh J. Bot. 42(2): 367-369, 2013 (December)